The Influence of Game-Based Learning on Mathematical Creative Thinking Ability and Self-Efficacy - Ade Dwi Oktaviani; Tian Abdul Aziz; Lukman El Hakim (Bibliotheca: Journal of Philosophy, 2025)
This study aims to describe and evaluate the impact of implementing Game Based Learning (GBL) on students’ mathematical creative thinking skills and self-efficacy. The method used in this study is a Systematic Literature Review (SLR), conducted through a search of relevant national and international scientific articles from several databases such as Google Scholar, ScienceDirect, DOAJ, and Jayapangus Press, with a publication range from 2020 to 2025. The search results yielded 10 primary articles that met the inclusion criteria and were analyzed based on the authors, year, journal, research method, and main findings. The analysis results indicate that the implementation of Game Based Learning has a positive effect on improving various aspects of students’ abilities, particularly in mathematical creative thinking, self-efficacy, learning motivation, problem-solving skills, and collaborative abilities. The use of digital learning media such as Kahoot!, Quizwhizzer, Gimkit, Wordwall, and Android-based games has proven effective in creating an interactive, competitive, and engaging learning environment. Most of the studies showed significant improvements with p < 0.05, indicating the high effectiveness of the GBL model in enhancing learning outcomes and student engagement.